PENGARUH PENAGIHAN PAJAK DENGAN SURAT TEGURAN TERHADAP PENCAIRAN TUNGGAKAN PAJAK (STUDI PADA SALAH SATU KOTA ADMINISTRATIF DI JAWA BARAT) - Caesarini Novianty; Iwan Sidharta (Jurnal Computech & Bisnis (e-Journal), 2022)
This study aims to find out and test how the relationship and the extent influence of the variable letter of reprimand on the disbursement of tax arrears. The data analysis model used in this study is a descriptive analysis to test and provide an overview of how the effect of a letter of reprimand on the disbursement of tax arrears in 2018-2020 at one of the Primary Tax Service Offices in the City of Administration in West Java. Based on the study results, the results of simple linear regression obtained the equation Y = 17.815 + 0.729; this shows that tax collection with a letter of reprimand has a positive effect on the disbursement of tax arrears. In the Pearson Product Moment Correlation test results from the research, it is 0.373 or 37.3%, which means that there is a low but still influential correlation between tax collection and a letter of reprimand on the disbursement of tax arrears. The coefficient of determination shows the number 0.139 or 13.9%, which means that tax arrears' disbursement is influenced by tax collection with a warning letter of 13.9%. In contrast, the remaining 86.1% disbursement of tax arrears is influenced by other factors not examined. Therefore, recommendations from research results should continually evaluate the tax collection action with a warning letter which refers to the number of warning letters issued that have never reached the maximum number of warning letters paid. The purpose of the evaluation is to reduce the amount of tax arrears each year. Keywords: Tax Collection, Warning Letter, Disbursement of Tax Arrears.